The big five personality traits and eating habits among female students at Zayed University - AlBlooshi, Sharifa; AlSabbah, Kawther; Thani, Shatha; Hijazi, Rafiq; Al Dhaheri, Ayesha S.; Zeb, Falak; Cheikh Ismail, Leila (Frontiers in Public Health, 2025)
BackgroundAdhering to healthy dietary habits is crucial for disease prevention and improving overall quality of life. Understanding how personality traits influence eating behaviors is essential for developing effective interventions aimed at promoting healthier eating habits. Personality traits are consistent behavioral patterns that individuals typically exhibit, and the Five-Factor Model (also known as the Big Five) is widely recognized as an effective framework for predicting personality traits.MethodsThis study analyzed the relationship between personality traits and eating behaviors among 425 female students using a cross-sectional design. Sociodemographic data and personality traits were assessed using an online questionnaire, while eating behaviors were evaluated with the validated Three-Factor Eating Questionnaire (TFEQ). Key aspects of eating behavior studied included cognitive restraint, disinhibition, and emotional eating. The findings provide insights into how personality characteristics may influence eating habits, offering potential implications for interventions targeting healthier eating behaviors.ResultsThe majority of participants scored highest on the personality trait of openness to experience. The study found that certain personality traits, particularly neuroticism and agreeableness, were linked to dietary habits. Specifically, personality traits were associated with emotional eating (p < 0.003), but not with cognitive restraint (p = 0.25) or disinhibition (p = 0.308). Participants with higher levels of agreeableness demonstrated significantly higher cognitive restraint (p = 0.041).ConclusionPersonality traits can influence eating habits, particularly emotional eating. However, further research is needed to identify individuals at risk for diet-related diseases and to determine the most effective intervention strategies. This study is the first of its kind conducted in the United Arab Emirates, contributing valuable insights into the relationship between personality traits and eating behaviors.